Traffic Conflict Technique-Based Setting Method of Freeway Climbing Lane - Gu Xin; Xiang Qiao Jun; Li Shen (MATEC Web of Conferences, 2016)
Speed of heavy vehicles is greatly reduced on upgrade sections due to their insufficient climbing capability, thus having great impact on traffic safety. Setting climbing lanes can solve this problem effectively. Considering China’s traffic composition and operational status, this paper proposed the traffic conflict technique-based setting method of freeway climbing lanes in order to set foundations for climbing lanes with the goal of promoting traffic safety. Based on large freeway upgrade section data and actual traffic characteristics, the paper built simulation models with VISSIM. 220 schemes were simulated by setting different road and traffic conditions of models. The paper then used Surrogate Safety Assessment Model (SSAM) to calculate traffic conflict, analyzed the influence of slope, slope length and mixed rate of heavy vehicles on traffic safety on upgrade sections. Finally, taking the reduction extent of the collision rate after setting climbing lanes as an indicator, this paper used K-means to classify the effectiveness level of the climbing lanes. The paper found the setting position and basis of the climbing lanes. The findings of this paper can provide support to effective decision making with regards to constructing future climbing lanes.